2010
DOI: 10.1007/s11242-010-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation and Well Testing Applied in Evaluating Reservoir Properties in a Deforming Longwall Overburden

Abstract: During longwall mining, the intact strata start to deform and fracture as the mining face progresses. Gob gas ventholes (GGVs) are drilled from the surface over a longwall panel before mining to capture methane from the fractured zone. Due to fracturing and bedding-plane separations, reservoir properties change extensively. This poses a major problem for venthole designers and methane control engineers and may become a safety and health concern for underground work force due to unexpected methane emissions: it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Karacan [7] predicted radii of investigations for operating GGVs as 578 and 2818 ft, depending on the locations, by use of pressure transient analyses of multirate drawdown test techniques. The results given in this paper also compare, within the order of magnitude, with the radius of investigation (~4000 ft) of a well in a completely different setting and known to produce from a bedding-plane separation [9] in a bounded gob reservoir.…”
Section: Integrating Performance Prediction Based On Dca Maps With Gimentioning
confidence: 74%
See 1 more Smart Citation
“…Karacan [7] predicted radii of investigations for operating GGVs as 578 and 2818 ft, depending on the locations, by use of pressure transient analyses of multirate drawdown test techniques. The results given in this paper also compare, within the order of magnitude, with the radius of investigation (~4000 ft) of a well in a completely different setting and known to produce from a bedding-plane separation [9] in a bounded gob reservoir.…”
Section: Integrating Performance Prediction Based On Dca Maps With Gimentioning
confidence: 74%
“…The properties of fractured zones, mainly permeability, are determined through conventional pressure-and rate-transient well test analyses techniques that are used systematically and routinely for oil and gas [2][3][4][5][6]. Results showed that permeabilities of bedding plane separations can be as high as 150 Darcies, with average permeabilities (including fractures and intact formations) within the slotted casing interval of GGVs varying between 1 Darcy and 10 Darcies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Karacan and Goodman (2011b) analyzed the multiple rate data of a GGV tested in such an environment. However, since the existence of bedding plane separation was known and its thickness and location were known, the model was set up for an infinite acting fracture where the flow field was linear towards the wellbore in the separation zone.…”
Section: Longwall Gob Gas Ventholesmentioning
confidence: 99%
“…During mining of N-F panels, average methane production from GGVs is about 200 Mscfd, as opposed to 500-600 Mscfd from GGVs of G-K panels. This difference may be related to various factors discussed in Karacan (2009a) and differences in properties of the gob as a reservoir (Karacan, 2009c;Karacan and Goodman, 2011b). Similarly, methane rate from BF-2 averages around 2500-3000 Mscfd, where it is 1500-2000 Mscfd from BF-3.…”
Section: Setting Of the Mining District Mined Panels And General Mementioning
confidence: 97%